Kadar Air Ekstrak Herba Sambiloto (Andrographis paniculata) pada Variasi Suhu Pengeringan - Erik Arya Tandi; Ratih Purwanti; Mir-a Kemila (Jurnal Permata Indonesia, 2021)
Sambiloto (Andrographis paniculate) is one of the plants that can be used as an anti-diabetic drug. Sambiloto herb extracts are packaged as herbal medicinal preparations in accordance with CPOTB procedures to meet quality requirements. One of the quality requirements of herbal medicine is water content < 10%. The purpose of this study was to determine the water content of the extract of Sambiloto herbs (Andrographis paniculate) at various drying temperatures. This research is a type of experimental research with a one shoot case study design. Sambiloto herb extract was made by percolation extraction method with 96% ethanol as solvent. The viscous extract obtained was added with starch binder in order to obtain dry herb extract. The dried extracts were analyzed for their water content before and after entering the drying procedure. The drying temperature was varied at 40◦C, 50◦C and 60◦C. The results showed that the water content before drying at 40C, 50◦C and 60◦C was 16.92%, 7.58%, 7.05% and 5.10%, respectively. Statistical test obtained a significant value of 0.000 <0.05 so it is significantly different. Conclusion : The drying temperature affects the water content of the extract of Sambiloto herbs (Andrographis paniculate) Keyword : Sambiloto, Water content, herbal extracts